Significant variations in tolerance to clothianidin and pirimiphos-methyl in Anopheles gambiae and Anopheles funestus populations during a dramatic malaria resurgence despite sustained indoor residual spraying in Uganda - Ambrose Oruni; Emmanuel Arinaitwe; James Adiga; Geoffrey Otto; Patrick Kyagamba; Joseph Okoth; Daniel Ayo; Jackson Rwatooro Asiimwe; Maato Zedi; John Rek; Kyle J. Walker; Ashlee Braithwaite; et al. (Parasites & Vectors)
Abstract Background A dramatic malaria resurgence occurred in areas of Uganda between 2020 and 2022, coinciding with the switch to clothianidin-based formulations for indoor residual spraying. During the resurgence, Anopheles funestus sensu lato (s.l.) numbers increased more than those of Anopheles gambiae s.l., but when an alternative insecticide, pirimiphos-methyl, was reintroduced in 2023, both malaria cases and An. funestus mosquito density fell. Methods In this study, we investigated possible causes of the resurgence by assessing (1) whether sufficient quantities of insecticide were sprayed, (2) the residual insecticide bio-efficacy against wild mosquitoes, and (3) the insecticide susceptibility of both key vector populations using standard test tube assays and wall cone assays. Results In 2023, after adjusting for extraction efficiency, 70–80% of the houses had optimal residual concentrations of insecticides (clothianidin > 0.3g/m2; pirimiphos-methyl > 0.5g/m2), with significant variations between sampling rounds and wall types. Mud walls had the lowest residual concentration of insecticides, and the lowest observed mortality in wall cone assays, compared to burnt bricks with plaster/cement/paint. In the studies of residual bio-efficacy, by World Health Organization (WHO) definitions, An. funestus s.l. showed resistance to clothianidin (< 80% mortality) up to 11 months, and susceptibility to pirimiphos-methyl (> 90% mortality) when exposed to wall surfaces up to 7 months post-spray. In WHO tube tests, variations were observed in susceptibility to clothianidin in An. funestus s.l. populations using dose– and time–response assays (80–98% mortality). In 2022, An. gambiae s.l. was largely susceptible to the clothianidin-based formulation Sumishield (85–90% mortality), although the levels dropped slightly in 2023 (60–85% mortality), mainly in mud and pole houses. In contrast, An. gambiae s.l. was highly susceptible with mild tolerance to the pirimiphos-methyl-based formulation Actellic (~ 80% mortality), and time–response assays showed that An. gambiae s.l. populations had very low knockdown and mortality at lower exposure time compared to An. funestus s.l. Regression models showed a positive association between residual insecticide concentration (RIC) and mortality in houses sprayed with Sumishield but not Actellic houses. Conclusions Despite the possible variations observed in spray operations, the study revealed that An. funestus s.l. exhibited a higher tolerance to clothianidin-based formulations compared to An. gambiae s.l., and this might have driven the malaria resurgence observed in Uganda. However, there are signals of An. gambiae s.l. resistance to pirimiphos-methyl, which will require further investigation and monitoring. Graphical Abstract